Aryne Annulations for the Synthesis of Carbocycles and Heterocycles: An Updated Review - Sarmah, Manashi; Hazarika, Hemanta; Gogoi, Pranjal (Synthesis, 2022)
Carbocycles and heterocycles are highly relevant structural moieties that have found countless applications in interdisciplinary areas. In this regard, the interesting chemistry of arynes has been embraced by researchers for the synthesis of structurally different polycyclic systems, i.e. carbocycles and heterocycles. In this review, we intended to provide a comprehensive overview on the annulative approach considering Kobayashi’s aryne intermediate as the key reactive species with diverse nucleophilic and electrophilic partners. The review highlights the different aryne annulation reactions adopted for the synthesis of carbocycles and heterocycles (covering articles mainly from around 2010), showcasing their viability towards broad range of substrates bearing diverse functionalities.1 Introduction2 Synthesis of Carbocycles3 Synthesis of Heterocycles4 Conclusions
Keywords: Kobayashi’s aryne; annulation; carbocycle; heterocycle; polyaromatic hydrocarbons